Sensitivity analysis of design parameters of a small solar-powered electric unmanned aerial vehicle - Rajendran, Parvathy; Smith, Howard (Taylor's University, Malaysia, 2018)
The design, fabrication, and operation costs of a solar-powered unmanned aerial vehicle (SUAV) only comprise a small fraction of the various aspects of satellite systems. Given the easy redeployment of SUAVs with a newly enhanced payload, many researchers have become interested in studying the potential of SUAVs as pseudo-satellites. However, research on the capability of a small SUAV to achieve year-round global perpetual operation remains in its infancy. The endurance of small SUAVs may be further improved by reducing system weight and power consumption. Therefore, sensitivity analyses are performed to determine the effects of payload, propulsion’s weight to power ratio, and solar module’s weight to area ratio on the weight and power consumption of a small SUAV. The outcome of this investigation is vital to avoid unnecessary investment on product development that may not significantly improve the performance and capabilities of SUAVs. The payload exerts the greatest effect on the maximum take-off weight of a SUAV, followed by the battery, structure, solar module, and propulsion weight. The weight to area ratio of the solar module should be prioritized in technological advancements to promote the endurance of SUAVs. In addition, small SUAVs will considerably benefit from improvements in the weight to power ratio of the propulsion.
Keywords: Battery; Electric motor; Endurance; Power Consumption; Solar; Solar powered UAV